PRODUKSI PENGETAHUAN SEKSUALITAS : REPRESENTASI PELECEHAN SEKSUAL REMAJA DI PUGER - Nur Idayati; Maulana Surya Kusumah (Universitas Negeri Malang, 2020)
In this article that focuses on issues of youth, sexuality and sexual harassment. The existence of culture in the reality of adolescent habits about permitting sexual harassment behavior. Besides sexuality is still considered taboo to be discussed in public spaces. Sociologically this phenomenon can be said as a form of failure of the construction of sexuality in adolescents. This assumption is supported by the knowledge of adolescent sexuality that allows sexual harassment and is considered a joke. Sexuality as a production of knowledge is taken from the point of view of adolescents and environments that have direct relations. The discourse of sexuality comes with a variety of operators. This article is the main issue narrated using the knife of Michel Foucault's analyst about sex, power and knowledge. In addition this study aims to describe the knowledge of adolescent sexuality in Puger. In its methodological consequences this article uses the Foucault genealogy to narrate the knowledge of adolescent sexuality. Researchers try to see how basic problems that arise can be solved by a historical framework. Then the key informants were teenagers / students from junior high schools (Public Schools) and senior high schools (Religious Schools) in Puger Kulon.Pada artikel ini akan fokus pada isu remaja, seksualitas dan sexual harassment. Secara konseptual argumentasi peneliti lebih merujuk pada kehidupan remaja hari ini. Adanya budaya dalam realitas kebiasaan remaja tentang diijinkannya perilaku pelecehan seksual. Selain itu seksualitas masih dianggap tabu untuk diperbincangkan di ruang publik. Secara sosiologis fenomena ini dapat dikatakan sebagai suatu bentuk kegagalan konstruksi seksualitas pada remaja. Asumsi ini didukung dengan adanya pengetahuan seksualitas remaja yang mengijinkan pelecehan seksual dan dianggap sebagai lelucon. Pengalaman remaja tentang pelecehan seksual di lingkungan sekolah seperti komentar seksual, lelucon, gerakan, serta menunjukkan video porno. Seksualitas sebagai suatu produksi pengetahuan diambil dari sudut pandang remaja serta lingkungan yang memiliki relasi secara langsung. Diskursus seksualitas hadir dengan ragam operatornya. Artikel ini menjadi isu utama yang akan dinarasikan dengan menggunakan pisau analisisi Michel Foucault tentang seks, kekuasaan dan pengetahuan. Selain itu penelitian ini bertujuan untuk mendeskripsikan pengetahuan seksualitas remaja di Puger. Pada konsekuensi metodologisnya artikel ini menggunakan genealogi Foucault untuk menarasikan pengetahuan seksualitas remaja.